Efficiency estimation of transport companies' activity - Vyskupaitis, Andrius (Transport, 2003)
In this article methodological subjects of activities efficiency research of the transport companies as well as other complex systems are analyzed. Methodically it is the most important to select estimation indexes of efficiency of searching object activities. After the system of indexes is formed, it is determined that it is more useful to use the system of technical economic indexes in order to estimate the level of efficiency of the activities of transport companies. It is so, because none of the separate indexes individually is able comprehensively to reflect the activities of transport systems or separate companies. Using the proposed method it is possible to research the great amount of objects according to numerous indexes. The main task is to form conditionally monolithic groups from the totality of objects. The level of activities of the objects in these groups should be similar. It would be possible to solve this task with the help of the image identification theory. The essence of this theory is to used necessary algorithm for the identification of searching objects signs. On this basis each object is reckoned in a certain monolithic objects group. Next step is the use of classification algorithms, which enable to classify the whole of searching objects. In this article you would fmd two main stages of classification problem solution. In the first stage the expansion of the objects into monolithic groups according to one of the indexes goes. The quality of this stage depends on the amount of the groups and on the selection of a concrete index. In the second stage the final objects expansion into monolithic groups according to the whole of selected technicaleconomic level indexes goes. Here is the manifold classification of the objects. Its results enable to determine the efficiency level of transport systems activities as well as to improve the quality of planning transport company's activities.First Published Online: 19 Dec 2011